Catalytic behavior of Pr1-xBa1+xCo2O6-δ in alkaline medium - Bangwal A.S.; Chauhan M.; Singh P. (My University, 2025)
In this work, a series of double perovskite oxide materials Pr1-xBa1+xCo2O6-δ (x = 0.05, 0.10, 0.15, and 0.20) was synthesized using the solid-state route method. Their catalytic activity and stability in 1 M KOH alkaline medium were investigated. The phase formation and structure of the prepared oxides were determined by Powder X-ray diffraction. The morphology of prepared catalysts was confirmed by SEM analysis. The catalytic performance of the prepared catalyst in alkaline solution was investigated using electrochemical measurements for both oxygen evolution reaction (OER) and oxygen reduction reactions (ORR). This series of double perovskite oxide materials exhibit catalytic activity for both OER and ORR. Pr0.90Ba1.10Co2O6-δ shows wonderful OER activity among all the catalysts with a specific capacitance of 598.40 F/g and double-layer capacitance of 38.94 mF/cm2. Power low gives a hint of oxide-ion intercalation pseudocapacitance in the Pr0.90Ba1·10Co2O6-δ. On the other hand, Pr0.95Ba1·10Co2O6-δ exhibits potential behavior for ORR. Overall, our findings highlight the combined effects of incorporating Ba into double perovskite PrBaCo2O6-δ in its behavior for OER and ORR. © 2022 Hydrogen Energy Publications LLC